Dissolution Enhancement of Raloxifene Using Water Soluble Carrier by Solid Dispersion Technique - Dhandapani, Nagasamy Venkatesh (Asian Journal of Pharmaceutics (AJP), 2018)
Raloxifene is a second-generation selective estrogen receptor modulator used in the treatment of osteoporosis in women. The drug is practically insoluble in water and exhibits exceptionally slow and intrinsic dissolution rate with poor bioavailability. In the present study, raloxifene and Î²-cyclodextrin (Î²-CD) solid dispersions were prepared with a view to study the effect and influence of Î²-CD on the solubility and dissolution rate of this poorly aqueous soluble drug. Phase solubility profile revealed that the solubility of raloxifene was significantly increased in the presence of Î²-CD and was classified as AL-type, indicating the possible 1:1 stoichiometric inclusion complex with a stability constant of 328.65 Mâˆ’1. Effect of variable such as drug: carrier ratio was studied. Physical characterization of the solid dispersion was characterized by Fourier transform infrared spectroscopy, differential scanning calorimetry, and X-ray diffraction studies. These studies revealed that a distinct loss of drug crystallinity in the solid dispersion is ostensibly accounting for enhancement of dissolution rate in distilled water containing 0.1% Tween 80. The scanning electron microscopy study revealed that all the binary systems appeared as agglomerates and exhibiting the presence of a homogenous solid phase which could also be responsible for the enhanced dissolution rate in comparison with the pure drug. The drug release from the prepared solid dispersion exhibited the first-order kinetics. Solid dispersion of raloxifene showed a 6.77 times fold increase in dissolution rate over the pure drug.